Holistic evaluation of knowledge management practices in large Indian software organisations. (19th June 2019) - Mathew, Asish Oommen; Rodrigues, Lewlyn L.R.
This research analyses the knowledge management (KM) implementation in India software organisations from the perspective of the knowledge workers. A holistic KM evaluation was conducted by capturing the perceptions of critical success factors, process capability, and the effectiveness of KM. The parameters of the study were developed by using content analysis. A questionnaire survey was conducted to capture the knowledge worker's perception of the eight generic dimensions of critical success factors, five dimensions of KM process capability and five dimensions of KM effectiveness. The data for this research was collected from 423 knowledge workers from 66 large software firms that were listed on the Bombay Stock Exchange (BSE). The perception of each factor was converted to knowledge management index (KMI) scores for interpretation. The results indicated that the overall implementation of KM in Indian software firms was in the right direction with above average KMI scores for all factors. The critical success factors, knowledge process capability factors, and knowledge management effectiveness parameters were ranked based on their perception scores.